KOTO TUO LAUTAN API: SEBUAH PERISTIWA PADA MASA PDRI DI SUMATERA BARAT (1948-1949) - M Reki Hidayat; Etmi Hardi (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This study discusses the incident of attacking and burning the houses of the Nagari Koto Tuo community, Lima Puluh Kota Regency by the Dutch in 1949. This event was one of various events during the Dutch Military Aggression II until the establishment of PDRI in Payakumbuh. The purpose of this study is to find out what is the role and involvement of Nagari Koto Tuo during the PDRI period and how the process until this nagari became the target of Dutch attacks. The research method to be used in this study is a historical research method consisting of four stages, namely, the first stage, namely heuristics, source criticism, interpretation and historiography. The results showed that Nagari Koto Tuo had direct involvement as a refugee route passed by the PDRI group who wanted to go to the Riau region and also as one of the battle power bases for the Lima Puluh Kota region.